Looking behind the label : global industries and the conscientious consumer - Bartley, Tim; Koos, Sebastian; Samel, Hiram; Setrini, Gustavo; Summers, Nik (Global research studies., 2015)
"What does it mean when consumers 'shop with a conscience' and choose products labeled as fair or sustainable? Does this translate into meaningful changes in global production processes? To what extent are voluntary standards implemented and enforced, and can they really govern global industries? Looking behind the Label presents an informative introduction to global production and ethical consumption, tracing the links between consumers' choices and the practices of multinational producers and retailers. Case studies of several types of products -- wood and paper, food, apparel and footwear, and electronics -- are used to reveal what lies behind voluntary rules and to critique predominant assumptions about ethical consumption as a form of political expression."--Provided by publisher